Supporting collaboration and knowledge sharing in building SLEs for ageing well: Using cognitive mapping in KMS design - Weck. M.; Gelashvili, T.; Pappel, I.; Ferreira, F. (Knowledge Management Research and Practice, 2022)
This article seeks to contribute to the existing body of knowledge management systems (KMS) literature by using cognitive mapping and demonstrating its usefulness in terms of context analysis for identifying the knowledge needs of multiple stakeholders and the appropriate characteristics of a KMS technology solution. Empirical data were collected through two case studies conducted in Finland and Estonia that used knowledge panel meetings to bring together knowledgeable experts who represented quadruple helix (QH) regional innovation actors involved in building smart living environments for ageing well (SLEaws). Adopting a multicriteria approach in both case studies, cognitive mapping as an important instrument of the strategic options development and analysis (SODA) methodology was used during the panel meetings of both cases to facilitate the decision making of the experts in developing an integrated framework or tool that can support KMS design.